1983
DOI: 10.1111/j.1943-278x.1983.tb00009.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognition and Suicide: A Methodological Review

Abstract: This article reviews the literature related to studies measuring various cognitive properties in suicidal patients. It provides a structural framework with which to classify the studies, and employs the categories of suicidal logic, cognitive style, social cognition, and cognitive control. The methodological issues discussed include: sample characteristics, operational definitions of suicidal behaviors, use of appropriate control groups, and the temporal nature of assessment. Improvements in experimental desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…This model later showed predictive utility for depression and suicidal ideation in college students (Priester & Clum, 1993). Arffa (1983) presented a critical review of the nascent field of cognition and suicide, commenting that, although methodological problems remained, "consistent differences in the cognition of suicidal and nonsuicidal groups have been demonstrated" (p. 117). While noting that some findings (e.g., field dependence) were inconsistent, she observed that "cognitive-rigidity (whether it is termed dogmatism, dichotomizing, hopelessness, or whatever) is patently implicated in suicide" (p. 118).…”
Section: Early Cognitive Insightsmentioning
confidence: 99%
“…This model later showed predictive utility for depression and suicidal ideation in college students (Priester & Clum, 1993). Arffa (1983) presented a critical review of the nascent field of cognition and suicide, commenting that, although methodological problems remained, "consistent differences in the cognition of suicidal and nonsuicidal groups have been demonstrated" (p. 117). While noting that some findings (e.g., field dependence) were inconsistent, she observed that "cognitive-rigidity (whether it is termed dogmatism, dichotomizing, hopelessness, or whatever) is patently implicated in suicide" (p. 118).…”
Section: Early Cognitive Insightsmentioning
confidence: 99%
“…However, given the abstractness of this construct, it has been conceptualized and operationalized in a variety of different ways (King et al, 2000). As a result, this idea has proven difficult to evaluate scientifically, and early empirical findings were mixed (see Arffa, 1983 for a review). Drawing upon cognitive and neuropsychological theories and research, some now argue that this apparent rigidity could reflect deficits in executive function (EF; e.g., see King et al, 2000 and Keilp et al, 2001).…”
mentioning
confidence: 99%
“…Goldney and Burville (1980) stress the importance of critically evaluating interpersonal relationships in order that intervention on a scientific basis may be offered; yet there have been no adequate empirical studies to date investigating the relationship of interpersonal problem‐solving skills to self‐poisoning behavior (Schotte & Clum, 1982). Studies into deficits in cognitive functioning have used, in the main, impersonal creativity tasks (Arffa, 1983). The cognitive functioning that characterizes self‐poisoning patients has been reported as rigid and constricted (Levenson, 1974; Neuringer, 1976; Patsiokas, Clum, & Luscomb, 1979).…”
mentioning
confidence: 99%
“…Schotte and Clum (1982) point to the need for research on the nature of the problem‐solving deficits in suicidal individuals as a prerequisite to the development of effective treatment strategies. In a comprehensive review of cognition and suicidal behavior, Arffa (1983) suggests that social cognition is a promising area for future research.…”
mentioning
confidence: 99%